On-Line Learning: Frontiers in the creation of learning communities - Davis, Mike; Denning, Kate (Proceedings of the International Conference on Networked Learning, 2000)
The aim of this paper is to look at the social and learning dynamics of computer mediated communication in postgraduate education. The research was conducted within the tradition of ethnographic action research and draws upon insights from the theory and practice of Adult Education, and from Social Anthropology.